Elaboración de un manual de funciones, reglamento de admisión y empleo y valuación de puestos por puntos, para la cooperativa de ahorro y crédito de la pequeña empresa Cacpe Yantzaza - Villacís Rojas, Andrea Isabel (2015)
This research work had as general objective to perform a "Manual of Functions, Rules of Admission and Employment and Jobs Valuation points to the credit union Small Business CACPE Yantzaza" to enable efficient management in the foundation, which gave rise to the title of this work. To meet this goal was necessary to use scientific, deductive, inductive, descriptive, analytical, synthetic and statistical methods and techniques of observation and the interview was applied to the manager and employee surveys working in the Cooperative Savings and Credit for Small Enterprises CACPE Yantzaza. In the results it begins with a historical overview of the company, then as part of diagnosis consist of the interview results and surveys the manager and employees of the cooperative. It is disclosed structured charts, which consist charges are based on the current reality of the company, then a manual functions where valuable and important information is presented with respect to each of the charges integrated developed the cooperative roles and responsibilities of each of the members of the cooperative, avoiding duplication of functions and allowing better organization in the cooperative. Furthermore, the valuation of positions, where the system is applied on points with their respective stages from defining factors to the valuation of jobs, where the following results were obtained was developed. The total points as the valuation is 5410.00 salaries paid to employees of the company amounts to $ 9,956.05 with these data the straight line equation was applied, which resulted in a slope of 1.86 based on the value above the salary adjustment with valuation factor of 1.84 in order to determine the new wage was performed. The revaluation was performed only charges were below the line of the salary adjustment, which in total amounted to 14 Counsel, Secretary, credit analyst, one assistant collections, operations assistant, assistant files, matrix cashier, bus station cashier, customer service one client 2 business services, customer service advisor, service attendant, guard matrix, guard ground terminal. Ending this point the rules of admission and employment took place, it will allow the cooperative to select the most suitable for any office where a vacancy arises in the future staff. Once the work completed it was determined the conclusions and recommendations being the most relevant to the selection of personnel for the credit union Small Business CACPE Yantzaza not be done according to established policies, resulting not recruit suitable staff for different positions that owns the cooperative and within the recommendations suggest considering Function Manual, Rules of Admission and Employment and Valuation of Posts. For Points, in order to systematically evaluate staff performance in office, which will determine whether it meets the requirements necessary for the various offices of the credit union